2015
DOI: 10.1091/mbc.e15-01-0055
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric formation of coated pits on dorsal and ventral surfaces at the leading edges of motile cells and on protrusions of immobile cells

Abstract: High-resolution, real-time, three-dimensional fluorescence microscopy imaging shows the absence of clathrin-coated pits and vesicles at the ventral surfaces of lamellipodia and lamellae at the front of migrating cells. In addition, the data support the model invoking net membrane deposition at the cell front of migrating cells due to an imbalance between endocytic and exocytic membrane flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 55 publications
4
54
0
Order By: Relevance
“…However, CHC depletion only partly inhibited the more rapid FA disassembly in Cul5-deficient cells (Figure 2—figure supplement 2a), suggesting that Cul5 inhibits a distinct mechanism of disassembly that is clathrin-independent. Consistent with this interpretation, clathrin-coated pits were missing from the leading lamellipodium of migrating Cul5-deficient cells (Figure 2—figure supplement 2b), as recently reported for other cell types (Kural et al, 2015). This suggests that Cul5 regulates FA disassembly through mechanisms unrelated to clathrin-mediated endocytosis.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, CHC depletion only partly inhibited the more rapid FA disassembly in Cul5-deficient cells (Figure 2—figure supplement 2a), suggesting that Cul5 inhibits a distinct mechanism of disassembly that is clathrin-independent. Consistent with this interpretation, clathrin-coated pits were missing from the leading lamellipodium of migrating Cul5-deficient cells (Figure 2—figure supplement 2b), as recently reported for other cell types (Kural et al, 2015). This suggests that Cul5 regulates FA disassembly through mechanisms unrelated to clathrin-mediated endocytosis.…”
Section: Resultssupporting
confidence: 89%
“…However, our evidence suggests that MT-dependent integrin endocytosis is not involved in the SFK-Cas FA disassembly pathway. Clathrin-coated pits are absent from the ventral surface of the leading edge of motile glioblastoma cells (Kural et al, 2015) and were absent from the long leading lamellipodium of Cul5-deficient MCF10A cells. Moreover, clathrin knockdown inhibited the slow FA disassembly in normal HeLa cells but not the rapid FA disassembly in Cul5-deficient HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…This cell line represents a physiologically relevant model to study JUNV biology because JUNV-induced Argentine hemorrhagic fever manifests with neurological symptoms (1). While they are less relevant, breast cancer SUM159 cells were used here because we have previously optimized gene-editing strategies to express fluorescently labeled endogenous proteins in these cells (27,33). Here we showed that we can also manipulate the genome of SVG-A cells by inserting a fluorescent EGFP tag into the N terminus of the endosomal small GTPases Rab5c and Rab7a (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we had to identify new human cellular models compatible with such techniques because the genome of Vero cells (derived from the green African monkey) has not been fully sequenced and at present is not suited for use in efficient gene-editing approaches. We had successful experiences in editing the genes of cells of the human breast cancer cell line SUM159 (27,32,33) and therefore evaluated SUM159 cells for permissiveness and compared them to the Vero and A549 cells routinely used in JUNV infection assays. In addition, we also tested SVG-A human astroglial cells as a potential host relevant for JUNV physiopathological studies.…”
Section: Characterization Of New Cell Line Models Suitable For Junv Imentioning
confidence: 99%
“…1). We have worked with over fifty different groups to apply these tools in areas including: mitotic spindle alignment during asymmetric stem cell division [2]; actomyosin contractions driving the initial gastrulation of C. elegans embryos [3]; binding kinetics of single transcription factor molecules to DNA in live stem cells [4]; dynamic, heterogeneous remodeling of P granule proteins in C. elegans embryos [5]; asymmetric formation of clathrin-coated pits on the dorsal /ventral surfaces at the leading edge of motile cells [6]; rapid 3D redistribution of actin in T cells during the formation for the immunological synapse [7]; and spatiotemporal quantification of microtubule growth tracks throughout the cellular volume at all mitotic stages [8].…”
mentioning
confidence: 99%